Determination of the surface sterilization protocol and optimization of ficus carica callus induction: Unveiling the potential of auxins and low kinetin concentration on callogenesis - Sin, Phin Yin; Tan, Suat Hian; Lim, Hooi Thong; Putri Shareen, Rosman; Karim, Md. Rezaul (AIP Conference Proceedings, 2025)
Ficus carica, commonly referred as fig, is a fruit-bearing tree that has high nutritional and medicinal value. Despite its potential, low proliferation rates and high susceptibility to contamination are the major challenges for the cultivation of F.carica. Micropropagation is the in vitro approach used for the propagation of fig trees that relies on effective surface sterilization and optimal plant growth regulators (PGRs) enriched in the culture medium. The objectives of this study were to determine the surface sterilization protocol for F. carica and to optimize the callus induction in F. carica using a combination of different auxins (naphthalene acetic acid and 2,4-Dichlorophenoxyacetic acid) and cytokinin (kinetin) at varied concentrations. In this study, four surface sterilization treatments were evaluated for their efficiency in minimizing the contamination percentage while enhancing the survival percentage of F. carica. Results showed that M3 treatment (70 % ethanol+20 % Clorox+two drops of Tween 20) showed the highest efficacy, resulting in a minimal contamination percentage of 20.8%, coupled with 66.7% of both leaf survival percentage and callus induction. For callus induction, a combination of kinetin and 2,4-D in the MS basal medium outperformed NAA+2,4-D, with the optimum concentration identified as 1.5 mg/L NAA+1.5 mg/L 2,4-D. Surprisingly, a lower concentration of kinetin (0.2 mg/L)+2.0 mg/L 2,4-D exhibited superior callus induction (100%) compared to higher kinetin concentrations (1.5 mg/L)+1.0 mg/L 2,4-D (94.44%). In conclusion, a lower cytokinin concentration proved optimal for maximum callus induction when combined with auxin, providing valuable insights for improving F. carica micropropagation protocols.